In search of a combined brucellosis and tuberculosis vaccine for cattle - Schurig, Gerhardt G.; Boyle, Stephen M.; Qublan, Hamzeh Al; Sriranganathan, Nammalwar (Austral Journal of Veterinary Sciences, 2021)
Bovine brucellosis is caused by Brucella abortus. The bacterial pathogen causes economic losses because it induces abortion in cattle. Vaccination of calves with live B. abortus strain 19 induces a certain level of protection but induces persistent antibodies against cell envelope lipopolysaccharide that make it difficult to Distinguish Infected from Vaccinated Animals (DIVA). Live vaccine B. abortus strain RB51 was developed to elimínate such interfering antibodies and therefore, facilitate the differentiation of infected from vaccinated animals and help in the eradication of the disease. Vaccination with strain RB51 induces levels of protection similar to strain 19 but neither of the two vaccines give complete protection. We have been working to enhance protection induced by strain RB51 vaccine. Protective Brucella antigens can be over-expressed in strain RB51 by introducing a plasmid containing the leuB gene and the genes encoding such antigens. To avoid the expression of antibiotic resistance genes, we produced a leuB deficient strain RB51 and introduced a plasmid containing the leuB gene and the genes to be over-expressed. This new strain maintains the plasmid and has induced significantly high protection levels in mice. In addition, it allowed the construction of an RB51 vaccine strain able to express Mycobacterium bovis protective antigens so that the vaccine could protect against brucellosis and tuberculosis simultaneously.